Teaching the speaking skill in Enterprise I to students at Thaibinh Economic and Technical College: challenges and recommendations = Dạy kỹ năng nói theo giáo trình Enterprise I " cho sinh viên trường Cao đẳng Kinh tế - Kỹ thuật Thái Bình: khó khăn và giả - Hoàng, Thị Hằng (University of Languages and International Studies, 2017)
42 p. + CD-ROM